2016
DOI: 10.5395/rde.2016.41.4.246
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-electrolyte drinks exhibit risks for human enamel surface loss

Abstract: ObjectivesThe aim of this investigation was to give insights into the impact of carbohydrate-electrolyte drinks on the likely capacity of enamel surface dissolution and the influence of human saliva exposure as a biological protective factor.Materials and MethodsThe pH, titratable acidity (TA) to pH 7.0, and buffer capacity (β) of common beverages ingested by patients under physical activity were analyzed. Then, we randomly distributed 50 specimens of human enamel into 5 groups. Processed and natural coconut w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
7
0
7
Order By: Relevance
“…Prevalence of erosion has greatly increased in the recent years due to the growing consumption of acidic carbonated soft drinks [11]. Soft drinks have many potential health problems, and can cause dental caries and enamel erosion [12,13]. The methodology of the present study was designed to simulate frequent soft drink consumption in presence of saliva [3].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of erosion has greatly increased in the recent years due to the growing consumption of acidic carbonated soft drinks [11]. Soft drinks have many potential health problems, and can cause dental caries and enamel erosion [12,13]. The methodology of the present study was designed to simulate frequent soft drink consumption in presence of saliva [3].…”
Section: Discussionmentioning
confidence: 99%
“…Enamel is the chief targeted tissue in the process of erosion and its destruction may have multiple etiological factors (4) . This in vitro research demonstrated the demineralizing effect of two commercially available energy drinks (EDs) on enamel of human dentition.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, exogenous factors results from regular consumption of acidic diet and beverages or from frequent intake of acidic drugs (3) . Unrestricted ingestion of carbonated soft beverages and high energy drinks (EDs) are among the most aggressive extrinsic causes of dental erosion (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Only one examiner performed the measurements to exclude possible errors. 23 The roughness of each sample was calculated by the arithmetic mean of five different measurements (µm). The alteration in surface roughness (∆Ra) was attained by the difference between the roughness before and after disinfection.…”
Section: Assessment Of Surface Roughnessmentioning
confidence: 99%